Salinity of the Modern Mahakam Delta, East Kalimantan - Ateng Surachmat (Ikatan Ahli Geologi Indonesia, 1999)
As one of the most prolific basins in Indonesia, Kutai Basin has been well explored. A lot of research has been run and millions of dollars has been spent in order to have a better understanding the basin setting. One of the key aspects to understand the Kutai basin is to fully understand the modern Mahakam Delta, including its sedimentary source, depositional energy, reservoir behaviour and some other important aspects.The salinity study of modern Mahakam was performed as part of the regional study to understand the modern delta better. The Mahakam river waters were samples during the LSU (Louisiana State University) Mahakam Delta Study in 1994, whilst the project itself was funded by VICO Indonesia, UNOCAL and TOTAL Indonesie.